EKSEKUSI SENGKETA PERDATA YANG TELAH BERKEKUATAN HUKUM TETAP (INKRACHT VAN GEWIJSDE) PADA PENGADILAN NEGERI PAYAKUMBUH - Rika Yeni Martasari; Syuryani Syuryani (Ensiklopedia of Journal, 2023)
Execution can be said to be the process or effort to implement a court decision that has permanent legal force, also known as res judicata or inkracht van gewijsde. Decisions that have permanent legal force are District Court decisions that are accepted by both parties to the dispute, settlement decisions, verstek decisions against which no verzet or appeal has been filed; decision of the High Court which was accepted by both parties and no cassation was requested; and the decision of the Supreme Court in terms of cassation. This study aims to find out how the execution is carried out and the problems encountered in executing civil disputes that have permanent legal force (inkracht van gewijsde) at the Payakumbuh District Court. This study used a sociological juridical (empirical) method using primary data and secondary data as the data source. From the results of the study it was found that there were still applications for the execution of civil disputes that were in arrears for quite a long time in the data register for requests for execution at the Payakumbuh District Court. These problems arose due to several factors, including the entry of civil cases of rebuttal or judicial review efforts to restrain the execution and the inability of the applicant for execution to deposit the execution down payment.